(untitled) (Economics and region, 2017)
UDC 504.062.2:338.242:336.226.44 Iryna Sotnyk, D.Sc. (Economics), Professor, Professor at the Department of Economics and Business Administration. Sumy State University. Modern directions of state policy improvement for development of renewable energy in Ukraine. The given paper is dedicated to the investigation of impact of annexation of the Crimea and the loss of state control over the territory of Anti-Terrorist Operation on renewable energy development and on energy independence of Ukraine. The author analyses dynamics of renewable energy sector development in Ukraine in 2012-2016 and concludes that violation of country’s territorial integrity negatively influenced on domestic renewable energy industry in 2015-2016. In 2016, Ukrainian “green” energy did not reached the level of 2014 by the main parameters of the sector: number of objects, their installed capacity and volume of electricity generation. At the same time, some progress in the industry’s development in 2016, as compared to 2015, is noticeable. Over the last 5 years (2012-2016), all of the key indicators of the renewable energy sector’s development show an increase that could be significantly higher in the absence of unfavorable external influences. Based on the executed analysis, the author proposes directions of state regulation improvement for renewable energy sector as follows: ensuring the development of renewable energy facilities in all regions of Ukraine, taking into account the complex criterion of economic, social and environmental feasibility; providing state support for the development of all types of renewables; wide involvement of population and its self-organization bodies into the process of creation and use of renewable energy facilities; expanding the range of state and local programs to increase energy efficiency and development of renewables. Keywords: renewable energy, state policy, economic stimulation, feed-in tariff, energy efficiency.